Empowering Community Digital Literacy through Participatory Artificial Intelligence Training Using Participatory Action Research in South Jakarta - Sarifah Agustiani; Riska Aryanti; Tri Wahyuni; Elah Nurlelah; Pristya Haliza Ramadhanti; Farah Diba Azkia (PT Agung Media Publisher, 2026)
Digital literacy has become a fundamental competency for communities in responding to the rapid advancement of Artificial Intelligence (AI) technologies. However, many community members still have limited knowledge and practical skills in utilizing AI productively, ethically, and responsibly. This community service program aimed to empower community digital literacy through participatory Artificial Intelligence training using a Participatory Action Research (PAR) approach in RT 05, Cikoko Urban Village, South Jakarta. The program was implemented through four stages of PAR, including problem identification, collaborative planning, participatory action, and reflection. Training activities consisted of interactive lectures, live demonstrations, guided hands-on practice, group discussions, and mentoring on AI applications, digital ethics, information verification, and online security. Program evaluation was conducted using observations, reflective discussions, and post-training questionnaires involving sixteen participants. The findings revealed three major outcomes. First, the participatory learning approach successfully increased community engagement, with 75% female participants and 69% of participants aged 12–20 years actively involved throughout the learning process. Second, the training achieved high participant satisfaction, with information delivery, training materials, presenter performance, and event organization each receiving an 81% satisfaction score. Third, the program significantly improved community digital literacy and readiness for AI adoption. Participants reported that the program provided substantial benefits (88%), increased their knowledge (81%), improved practical AI utilization skills (81%), and enhanced their overall satisfaction (81%), while sustainable technology utilization, practical relevance, systematic implementation, and willingness to participate in future activities each achieved 75% positive responses.